Language Style Applied on Indonesian Beauty Products in Digital Advertisements - Halim, Abd; Halim, Nur Mutmainna (Elite : English and Literature Journal, 2023)
In modern today, people compete to beautify themselves since being beauty has become a primary needs for every woman, even for a man. Besides for personal reason such as taking care of themselves, very often because it is caused by demands of work that requires fine appearance. For now, there are lots of beauty products that are easily obtained from online or offline markets. To support each products, each company needs certain marketing technique to attract consumers. This research aims to investigate language style used in some advertisements for Indonesian beauty products. There were total of 10 advertisements of 5 Indonesian beauty brands investigated in this study. Researchers used note-taking as an instrument and applied purposive sampling technique. Result of this study reveals that from several language style found in those advertisements, hyperbole appeared the most with 33 times appearance. Hyperbole is a kind of figure of speech that conceive heightened impact through the using, or even repetition, of purposeful exaggeration. This language style is often boldly overstated claims to emphasize things. Thus, most of beauty brands by locals investigated in this study used hyperbolic technique to advertise their products.